Peaks of in situ N2O emissions are influenced by N2O‐producing and reducing microbial communities across arable soils. (13th September 2017) - Domeignoz‐Horta, Luiz A.; Philippot, Laurent; Peyrard, Celine; Bru, David; Breuil, Marie‐Christine; Bizouard, Florian; Justes, Eric; Mary, Bruno; Léonard, Joël; Spor, Ayme
Abstract: Agriculture is the main source of terrestrial N2 O emissions, a potent greenhouse gas and the main cause of ozone depletion. The reduction of N2 O into N2 by microorganisms carrying the nitrous oxide reductase gene ( nosZ ) is the only known biological process eliminating this greenhouse gas. Recent studies showed that a previously unknown clade of N2 O‐reducers ( nos Z II) was related to the potential capacity of the soil to act as a N2 O sink. However, little is known about how this group responds to different agricultural practices. Here, we investigated how N2 O‐producers and N2 O‐reducers were affected by agricultural practices across a range of cropping systems in order to evaluate the consequences for N2 O emissions. The abundance of both ammonia‐oxidizers and denitrifiers was quantified by real‐time qPCR, and the diversity of nosZ clades was determined by 454 pyrosequencing. Denitrification and nitrification potential activities as well as in situ N2 O emissions were also assessed. Overall, greatest differences in microbial activity, diversity, and abundance were observed between sites rather than between agricultural practices at each site. To better understand the contribution of abiotic and biotic factors to the in situ N2 O emissions, we subdivided more than 59, 000 field measurements into fractions from low to high rates. We found that the low N2 O emission rates were mainly explained by variation in soil properties (up to 59%), while the high rates were explained by variation in abundance and diversity of microbial communities (up to 68%). Notably, the diversity of the nos Z II clade but not of the nos Z I clade was important to explain the variation of in situ N2 O emissions. Altogether, these results lay the foundation for a better understanding of the response of N2 O‐reducing bacteria to agricultural practices and how it may ultimately affect N2 O emissions. Abstract : We investigated how N2 O‐producers and N2 O‐reducers were affected by agricultural practices across a range of cropping systems and how peak and baseline N2 O emissions were related to these microbial communities, We found that the low rates were mainly explained by variation in soil properties (up to 59%), while the high emissions were explained by variation in abundance and diversity of microbial communities (up to 68%). Notably, the diversity of a recently discovered clade of N2 O‐reducers ( nos ZII) was important to explain the variation of in situ N2 O emission fractions. Altogether, these results lay the foundation for a better understanding of the response of N2 O reducing bacteria to agricultural practices and how it may ultimately affect N2 O emissions.